Analysis of Novel Care Management Programs in Primary Care: An Example of Mixed Methods in Health Services Research. (January 2019) - Holtrop, Jodi Summers; Potworowski, Georges; Green, Lee A.; Fetters, Michael
While health services researchers are using mixed methods research in large-scale studies with "big data" and incorporating data transformation for merging qualitative and quantitative data sets, these developments are not widely known to the broader mixed methods research community. Our purpose in this article is to introduce health services research to the broader mixed methods audience, to examine the potential for novel innovations in mixed methods research procedures, and to illustrate these points through a project on care management that used a convergent mixed methods design. In addition to traditional analytical procedures, we illustrate two qualitative to quantitative data transformation procedures, one using normalization process theory and a second, fuzzy set qualitative comparative analysis.